Validación del instrumento "Computer Vision Syndrome Questionnaire (CVS-Q)" para la evaluación del síndrome visual informático en personal de salud de Lima. - Aguilar-Ramírez, María Del Pilar; Meneses, Giovanni (Revista Medica Herediana)
Objectives: To validate and to determine the reliability of the computer vision syndrome questionnaire (CVS-Q) for the evaluation of the informatic visual syndrome in health care personnel in Lina. Methods: cross-sectional study carried-out in 82 health care workers. The validity of the instrument was evaluated by expert evaluation using the Aiken's V statistical method; construct validity was evaluated by factorial analysis; discriminant validity by the operator-receptor curve (ORC) contrasted with CSSV17 questionnaire; internal consistency by Cronbach's alpha and Spearman's Rho and intraclass coefficient correlation with 95% CI to evaluate test and r-test reliability. SPSS version 2.0 for Windows was used to process data. Results: Aiken's V obtained 100%; factorial analysis found 3 components that explained 69.455% of total variance. The ORC area was 0.889 [(0.845-0.934); IC=0.95] (p=0.000), sensitivity 72.22% and specificity of 100%. Cronbach's alpha was 0.939, Rho de Spearman 0.884 (p=0.000) and CCI 0.856 [(0.777 -- 0.907); IC=0.95] (p=0.000). Conclusions: The CVS_Q is valid and reliable to be used in health care workers with good psychometric properties.